Advances and Perspectives on Bioelectronic and Atomic Nanogenerators for Anticancer Therapy - Massimo Mariello (Nanoenergy Advances, 2025)
Nowadays, due to improvements in living standards, more attention is reserved to all-around disease prevention and health care. In particular, research efforts have been made for developing novel methods and treatments for anti-cancer therapy. Self-powered nanogenerators have emerged in recent years as an attractive cost-effective technology to harvest energy or for biosensing applications. Bioelectronic nanogenerators can be used for inducing tissue recovery and for treating human illness through electrical stimulation. However, there is still a lack of comprehensive cognitive assessment of these devices and platforms, especially regarding which requirements must be satisfied and which working principles for energy transduction can be adopted effectively in the body. This review covers the most recent advances in bioelectronic nanogenerators for anti-cancer therapy, based on different transducing strategies (photodynamic therapy, drug delivery, electrical stimulation, atomic nanogenerators, etc.), and the potential mechanisms for tissue repair promotion are discussed. The prospective challenges are finally summarized with an indication of a future outlook.